The sociological themes in french as a foreign language class - Bikić-Carić, Gorana (Array, 2013)
This research study consists of two parts. Initially, we were focused on analyzing sociological themes in French language textbooks. Results showed that there is a basis for introducing sociological themes in French language classes. Namely, all the defined themes already appear in textbooks. The theme „Culture“ appears much more than any other theme. The theme „Religion“ appears the least. In the second part of the study, we were focused on examining students attitudes and preferences towards sociological themes in general, with a special emphasis on themes which, according to our texbook content analysis. It was shown that students mostly hold positive attitudes towards French language classes and sociology. Furthermore, it was mainly not difficult for them to understand and acquire sociology class content and there is no sociological theme they distinctly did not like. Of all the themes they could explore in French language classes, students would most like to explore the theme „Culture“ and they would least like to explore the theme „Politics“. These data are precious beacuse they give us objective information about students interests. This information can be useful to single out further goal of encouraging interdisciplinarity and a holistic approach to teaching and tuition.